PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI CREAMBATH DI SMK LABSCHOOL UNESA 1 SURABAYA - Nirmala Agustin; Biyan Yesi Wilujeng; Dewi Lutfiati; Nieke Andina Wijaya (Jurnal Tata Rias, 2025)
Effective learning models have an important role in supporting the success of the learning process, so that it can improve student learning outcomes. The purpose of this study was to determine: 1) The syntax implementation of the quantum teaching learning model; 2) Student activiity; 3) Learning outcomes; and 4) Student responses. The research method used was quantitative, with a pre-experimental approach using one group pre-test and post-test design. The subjects of this study were 30 class X TKKR students. The sampling technique used purposive sampling. Data collectiion technique consisted 1) Observation, 2) Test; 3) Questionnaire. The data analysis technique for syntax implementation, student activity, affective learning outcomes, psychomotor and student responses used the average, while the analysis of cognitive learning outcomes improvement used the Wilcoxon signed ranks test assisted by SPSS version 22. The results showed: 1) Analysis of syntax implementation was 100%; 2) Analysis of activiity obtained an average 3.76; 3) Analysis of cognitive learning outcomes obtained an average pre-test score of 65.1 and a post-test score of 85.8, the results of the hypothesis test obtained a Sig. (2-tailed) value of 0.000 <0.05, it was concluded that there was a significant difference in cognitive learning outcomes between before and after the quantum teaching learning model was implemented. Affective learning outcomes obtained an average of 3.70, psychomotor learning outcomes obtained an average of 3.74 which means that affective and psychomotor learning outcomes are very good; and 4) studentt responses obtained an average of 4.59 which means very good. So it can be concluded that there is an increase in student learning outcomes between before and after the implementation of the quantum teaching learning model with a very good response. Keywords: Quantum Teaching, Creambath, Learning Outcomes.